Exploring digital libraries foundations, practice, prospects - Calhoun, Karen (Facet Publishing, 2014)
A highly readable and in-depth treatment of the digital library arena that provides an up-to-date overview of the progress, nature and future impact of digital libraries, from their collections and technology-centred foundations over two decades ago to their emergent, community-centred engagement with the social web.